Wear-resistant and environment-friendly laminated composite sheet and preparation method thereof
By using an environmentally friendly steel paper laminated composite material with a hydrophobic structure when the steel paper is combined with natural fibers, and using the bonding layer of phenolic resin and/or latex emulsion, the problem of poor bonding performance is solved, and the production of high wear resistance and environmentally friendly materials is achieved.
Patent Information
- Application Number
- CN202411458612.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-10-18
AI Technical Summary
In the prior art, when steel paper is combined with fiber webs such as natural plant fibers, the adhesive performance of the adhesive is poor, which limits the production and application of high wear resistance steel paper laminated composite materials.
The environmentally friendly steel paper laminated composite material based on natural fibers is used, including an environmentally friendly steel paper layer, an environmentally friendly fiber layer and an adhesive layer, wherein the steel paper layer and fiber layer have a hydrophobic structure, and the adhesive layer components include phenolic resin and/or latex emulsion.
It realizes high-resistance product materials that are environmentally friendly, renewable and have excellent wear resistance, and are suitable for the field of composite materials.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of steel paper processing, in particular to a multi-layer structure, and more particularly to a wear-resistant and environment-friendly laminated composite sheet and a preparation method thereof. Background Art
[0002] As a special paper, steel paper is made of cellulose and its derivatives as raw materials, and metal salts with strong swelling and gelling properties on cellulose are used as treatment agents to treat and laminate steel paper base paper to obtain modified processed paper. In the field of industrial manufacturing, steel paper is usually further compounded with other materials to form composite sheet products.
[0003] In some applications, steel paper needs to be combined with natural fiber webs to form high-strength and wear-resistant materials. With the strengthening of environmental protection awareness, the raw materials for the production of steel paper are gradually replaced by environmentally friendly materials such as natural source materials such as plant fibers. On the other hand, jute fiber, as a natural plant fiber, has excellent biodegradability, low density, good mechanical properties and renewability, making it an ideal sustainable reinforcement material and has gradually attracted widespread attention in the field of composite materials. However, the poor bonding performance of the adhesive when combining steel paper with fiber webs such as natural plant fibers limits the production and application of high-wear-resistant steel paper laminated composite materials.
[0004] The information in the background technology is only for illustrating the general background of the present invention and should not be regarded as admitting or suggesting in any form that such information constitutes the prior art known to a person skilled in the art. Summary of the invention
[0005] In order to solve at least some of the technical problems in the prior art, the present invention provides an environmentally friendly steel-paper laminated composite material based on natural fibers as raw materials, which is not only environmentally friendly and renewable, but also has excellent wear resistance and can be used as a material for high-durability products. Specifically, the present invention includes the following contents.
[0006] According to a first aspect of the present invention, there is provided a wear-resistant and environment-friendly laminated composite sheet, comprising an environment-friendly steel paper layer, an environment-friendly fiber layer and a bonding layer between the steel paper layer and the environment-friendly fiber layer, wherein the side of the environment-friendly steel paper layer and / or the environment-friendly fiber layer in contact with the bonding layer has a hydrophobic structure, and the components of the bonding layer include phenolic resin and / or latex emulsion.
[0007] In certain embodiments, according to the wear-resistant and environment-friendly laminated composite sheet of the present invention, the environment-friendly fiber layer comprises a jute fiber mesh, and the content of the jute fiber mesh is greater than 70% by weight.
[0008] In certain embodiments, according to the wear-resistant and environmentally friendly laminated composite sheet of the present invention, the raw materials of the environmentally friendly steel paper layer include 90-95 parts by weight of long fibers and 5-10 parts by weight of short fibers, wherein the long fibers are cotton wool fibers with a length of 2-25 mm, and the short fibers are wood pulp fibers with a length of 1-2 mm.
[0009] In certain embodiments, according to the wear-resistant and environment-friendly laminated composite sheet of the present invention, the Kappa number of the wood pulp fiber is 10-20.
[0010] In certain embodiments, according to the wear-resistant and environment-friendly laminated composite sheet of the present invention, the thickness of the environment-friendly steel paper layer is 1-5 mm, and the density is 1-2.5 kg / dm 3 .
[0011] In certain embodiments, the wear-resistant and environmentally friendly laminated composite sheet according to the present invention further comprises a glass fiber layer, wherein the glass fiber layer is bonded to the environmentally friendly steel paper layer and / or the environmentally friendly fiber layer by using a binder precursor.
[0012] In certain embodiments, according to the wear-resistant and environmentally friendly laminated composite sheet of the present invention, the hydrophobic structure is formed by treating the environmentally friendly steel paper layer or the environmentally friendly fiber layer with a treatment liquid at 20-35°C for 1-4 hours, and then washing and drying, wherein the treatment liquid contains 0.1-2mM cerium salt and 20-50% acrylamide.
[0013] In certain embodiments, according to the wear-resistant and environment-friendly laminated composite sheet of the present invention, the bonding layer is formed by curing the bonding agent precursor in contact with the environment-friendly steel paper layer and the environment-friendly fiber layer.
[0014] In certain embodiments, according to the wear-resistant and environmentally friendly laminated composite sheet of the present invention, the binder precursor comprises 70-85 parts by weight of phenolic resin and / or latex emulsion, 25-30 parts by weight of organic solvent and 0-5 parts by weight of cross-linking agent.
[0015] A second aspect of the present invention provides a method for preparing a wear-resistant and environmentally friendly laminated composite sheet, which comprises the following steps:
[0016] (1) treating the environmentally friendly steel paper layer and / or the environmentally friendly fiber layer with a treatment solution, wherein the treatment solution comprises 0.1-2 mM cerium salt and 20-50% acrylamide; and
[0017] (2) Next, a binder liquid is coated on the surface of the steel paper, and the environmentally friendly fiber layer is covered on the steel paper coated with the binder precursor, and a laminated composite sheet is obtained by pressing and curing, wherein the binder precursor comprises 70-85 parts by weight of a phenolic resin and / or a latex emulsion, 25-30 parts by weight of an organic solvent, and 0-5 parts by weight of a cross-linking agent.
[0018] The environment-friendly steel-paper laminated composite material of the present invention adopts natural fiber as raw material, which is not only environmentally friendly and renewable, but also has excellent wear resistance and can be used as a material for high-durability products. DETAILED DESCRIPTION
[0019] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0020] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that the upper and lower limits of the scope and each intermediate value therebetween are specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0021] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as commonly understood by those skilled in the art to which the invention belongs. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0022] Herein, the term "laminated composite sheet" refers to a sheet of a multi-layer structure formed by bonding steel paper and at least one other material layer by chemical reaction and / or pressure. The other material layer includes at least one natural fiber layer.
[0023] Herein, the term "natural fiber layer" refers to a layered structure formed by fibers of natural origin, and the fibers of natural origin are not limited, including but not limited to woody plant fibers, herbaceous plant fibers, etc. In certain embodiments, the natural fiber of the present invention is jute fiber.
[0024] In this article, the term "steel paper", sometimes also called "hardened paper" or "paper steel", refers to a high-hardness special paper made of fiber material. It has excellent elasticity, toughness, wear resistance and corrosion resistance, as well as good electrical insulation and mechanical strength. It can be used as mechanical parts such as gaskets.
[0025] Herein, the term "slurry composition", sometimes referred to as "slurry" or "paper stock", is a fibrous substance obtained by processing. Generally, the slurry composition further includes water to form a mixture. According to the fiber components of the slurry, the slurry is divided into plant fiber slurry, such as wood pulp (or wood fiber pulp), grass pulp (herbaceous plants such as stem fiber pulp), or inorganic material fiber slurry, such as glass fiber pulp. Generally, the slurry composition is a mixture containing multiple fibers, wherein inorganic material fibers are usually used as supplementary fibers.
[0026] Herein, the term "length", when used as a fiber characteristic, generally refers to the fiber length of the initial raw material, especially the average length. During the pulp processing, different processing conditions may cause different degrees of degradation, shortening, etc. of the length of the initial raw material fiber.
[0027] The present invention provides a wear-resistant and environment-friendly laminated composite sheet, which comprises a steel paper layer, an environment-friendly fiber layer and a bonding layer located between the steel paper layer and the environment-friendly fiber layer, wherein the sides of the steel paper layer and the environment-friendly fiber layer in contact with the bonding layer have a hydrophobic structure, and the components of the bonding layer include phenolic resin and / or latex emulsion.
[0028] Steel paper layer
[0029] The steel paper layer of the present invention refers to a sheet steel paper, which can be prepared from any natural source fiber. In an exemplary embodiment, the steel paper of the present invention is prepared from a natural fiber slurry composition, which includes two fibers of different lengths, namely long fibers and short fibers, preferably, the short fibers have a harderness than the long fibers. The present invention has found that when the long fibers and the short fibers are respectively hydrophilic fibers, preferably the hydrophilic properties of the two fibers are the same or similar, it is more conducive to promoting the combination between the two different fibers, thereby improving the tensile strength of the steel paper.
[0030] The long fiber of the present invention refers to a fiber having a longer length relative to another fiber in the steel-paper pulp composition. The length of the long fiber is generally controlled within the range of 2-25 mm, such as 3 mm, 5 mm, 6 mm, 8 mm, 10 mm, 12 mm, 15 mm, 16 mm, 18 mm, 20 mm, 22 mm, and 24 mm. Those skilled in the art will appreciate that the above length range is only exemplary, and other suitable lengths may be selected as required, such as 26 mm, 27 mm, 28 mm, 29 mm, 30 mm, etc. Preferably, the long fiber of the present invention is a flexible fiber, that is, it is more flexible than the short fiber.
[0031] In the present invention, the amount of the long fibers is 90 to 95 parts by weight, such as 91 parts by weight, 92 parts by weight, 93 parts by weight, 94 parts by weight, and 95 parts by weight. When the amount of the long fibers is within the above range, the contact between the long fibers can be ensured, while the regulating effect of the short fibers can be fully exerted.
[0032] In certain embodiments, the long fibers of the present invention are absorbent cotton fibers. Compared with non-absorbent cotton fibers, the combination of absorbent cotton fibers and the short fibers of the present invention can further improve the insulation performance of the steel paper fiber. The reason for this is unclear and is not bound by theoretical explanations. It is speculated that the possible reason is that the absorbent cotton fibers have a higher hydrophilicity, which is comparable to the hydrophilicity of the short fibers, especially wood pulp fibers, which is conducive to the combination of the fibers during hot pressing, thereby improving the strength and thus improving the insulation.
[0033] The length of the staple fibers of the present invention is generally selected in the range of 1-2 mm. In certain embodiments, the length of the staple fibers of the present invention is 1 / 3 to 1 / 10 of the length of the long fibers, such as 1 / 4, 1 / 5, 1 / 6, 1 / 7, 1 / 8, 1 / 9, etc.
[0034] In the present invention, preferably, the short fibers have a higher hardness, which may also be referred to as hard fibers, so that when forming steel paper pulp, the hard fibers can be randomly dispersed among a plurality of long fibers and promote bonding between the fibers during subsequent processing.
[0035] In the present invention, the amount of the short fibers is 5-10 parts by weight, such as 6 parts by weight, 7 parts by weight, 8 parts by weight, and 9 parts by weight. When the amount of the short fibers is within the above range, the short fibers can give full play to the hardness of the short fibers without affecting the bonding between the long fibers. If the amount of the short fibers is too high, the short fibers tend to be dispersed in large quantities between the long fibers, which is not conducive to improving the contact and bonding between the long fibers, affecting the toughness of the steel paper. On the other hand, if the amount is too low, the long fibers tend to be excessively contacted, which is not conducive to improving the hardness of the steel paper.
[0036] In certain embodiments, the short fibers of the present invention are wood pulp fibers. That is, fibers made from woody plants as raw materials. Wood pulp fibers can be virgin wood pulp, recycled wood pulp, or a mixture of the two in any proportion. The type of woody plant used as the raw material is not limited, and any woody plant known in the art can be selected, and examples thereof include but are not limited to broad-leaved plants such as birch, poplar, basswood, eucalyptus, maple, and coniferous plants such as fish-scale spruce, sand pine spruce, stinking fir, Korean pine, larch, and masson pine.
[0037] In certain embodiments, the wood pulp fiber of the present invention preferably has a kappa number of 5-20, such as 6, 7, 8, 9, 10, 12, 14, 15, 16, 18, etc. The present invention has found that when the kappa number is within the above range, the insulation performance of the steel paper produced can be greatly improved, and the density is higher. If the kappa number is too high, the insulation performance of the steel paper tends to decrease significantly.
[0038] The steel paper layer of the present invention can be prepared by known methods, and an exemplary preparation method includes but is not limited to the following steps:
[0039] (1) the slurry composition is passed into a pulping machine for pulping, then passed into a stock preparation box for mixing, further diluted and / or purified, and dehydrated by a paper machine to form a wet paper web, and the water content is controlled within a range of 4-8% by pressing and drying to obtain steel paper base paper;
[0040] (2) soaking the multi-layer steel paper in a solution for 1-10 minutes, wherein the solution is a zinc chloride solution with a concentration of 50-80% by weight;
[0041] (3) heating and pressurizing the soaked multi-layer steel paper base paper to form a semi-finished product;
[0042] (4) The product is aged at 20-40°C, desalted and dried to obtain environmentally friendly high-insulation steel paper.
[0043] Those skilled in the art will appreciate that the numbers (1), (2), etc. herein are only for the purpose of distinguishing different steps and do not indicate the order of the steps. As long as the purpose of the present invention can be achieved, the order of the above steps is not particularly limited. In addition, two or more of the above steps may be combined or performed simultaneously. In addition, those skilled in the art will appreciate that other steps or operations may be included before or after the above steps (1)-(4), or between these arbitrary steps, such as further optimizing and / or improving the method described in the present invention. For example, optionally, the present invention further comprises:
[0044] (5) before step (1), further comprising the step of adjusting the kappa number of the short fibers to 5-20;
[0045] (6) After step (4), the step of further shaping by a calender is included.
[0046] Step (1) of the present invention is a step for obtaining steel paper base paper, specifically, comprising allowing the pulp composition to enter a pulping machine for pulping treatment, then enter a pulping box for mixing, further undergoing dilution and / or purification treatment, and undergoing dehydration treatment through a papermaking machine to form a wet paper web, and controlling the water content in the range of 4-8% through pressing and drying to obtain steel paper base paper.
[0047] In the present invention, beating is performed in a pulping machine to increase the flexibility and interweaving of the fibers. The beating can be performed using a disc refiner, a conical refiner, or the like. The beating degree is controlled to be 15-25°SR, such as 16, 18, 20, 22, 24°SR; the wet weight is 8-18g, such as 9, 10, 12, 14, 16g, or the like. When preparing the slurry, the slurry is diluted to a solid content of 40-60% by weight. The purification treatment is used to remove fine impurities and particles. The purification method is not limited, and can be performed by, for example, precipitation, filtration, or flotation. Precipitation is the process of causing impurities to settle to the bottom by gravity. Filtration is the process of using filter media such as filter cloth or filter screen to intercept impurities. Flotation is the process of using bubbles to bring impurities to the surface of the slurry and remove them. The present invention can use any of the above methods or a combination of multiple methods for purification.
[0048] In the present invention, dehydration is a process of removing moisture from a mesh by vacuum to form wet paper. Pressing in the present invention further removes moisture. After pressing, the paper is transferred from the wet mesh to a wet machine, where heat transfer is used to achieve the purpose of drying, and then hot air drying is used to form base paper. In the present invention, the wet mesh can reduce the damage to the wet paper during the transfer process and maintain the flatness of the paper. The wet paper undergoes a wetting process on the wet mesh, which makes the cellulose fibers more tightly bonded, which is beneficial to the heat transfer effect in the subsequent drying process.
[0049] Next, it is dried by heat transfer in a wet press. The wet press is the main equipment used for paper drying. The wet paper is heated by hot rollers and hot air to evaporate the water in the paper. In the wet press, the wet paper is fed into the pressing area between the hot rollers. Under high pressure and high temperature, the water is squeezed out of the paper, making the surface of the paper dry. At the same time, the hot air heats the paper to increase the heat transfer effect and speed up the paper drying.
[0050] Step (2) of the present invention is a gelling treatment step, specifically, comprising soaking the multi-layer steel paper base paper in a chemical solution for 1-10 minutes, such as 1 minute, 2 minutes, 2.5 minutes, 3 minutes, 3.5 minutes, etc.
[0051] In the present invention, gelation is performed in a gelation tank, and the temperature during gelation is not limited, for example, the gelation can be performed by immersion in the range of 15-40° C. Exemplary gelation temperatures include room temperature, 30° C., 35° C., 36° C., etc. The liquid medicine used in the present invention is generally a zinc chloride solution with a concentration of 50-80% by weight, preferably, the concentration of zinc chloride is 55-75% by weight, such as 60% by weight, 65% by weight, 70% by weight, etc.
[0052] Step (3) of the present invention is a step for preparing a semi-finished product, specifically, comprising heating and pressurizing the soaked multi-layer steel paper base paper to form a strong bond between the layers. Heating and pressurizing can be performed separately or simultaneously. Heating and pressurizing at the same time is more conducive to the bonding between the base paper layers, and is therefore preferred. The heating temperature of the present invention is generally 30-90°C, for example, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, etc. When heating at high temperature, it is preferred to heat under wet conditions. The pressurization of the present invention is generally performed by a pressure roller, and the pressure size is not limited.
[0053] The step (4) of the present invention is an aging and desalting treatment step, which includes aging treatment at 20-40°C, desalting treatment, and drying to obtain environmentally friendly high-insulation steel paper.
[0054] In the present invention, the aging treatment is carried out in an aging furnace, and the aging temperature is generally controlled at 25-40°C, such as 30°C, 32°C, 25°C, etc. The aging time is generally 30-120 minutes, such as 40 minutes, 50 minutes, 60 minutes, 70 minutes, 80 minutes, 90 minutes, etc. The aging time is generally related to the aging temperature. Generally, when the aging temperature is low, the aging treatment time is appropriately extended.
[0055] In the present invention, the desalination treatment includes allowing the steel paper to enter a plurality of cleaning tanks with gradually decreasing concentrations and finally pure water for desalination treatment, and the zinc chloride concentrations in the cleaning tanks are 60%, 30%, 15%, 8%, 4%, 2%, 1%, 0.5%, 0.05%, and 0. The desalination treatment time of each cleaning tank is controlled within 20-60 minutes, thereby making the surface of the steel paper smoother and more delicate. The steel paper is dried.
[0056] In certain embodiments, the steel paper of the present invention has a higher specific gravity and a higher insulation strength than conventional steel paper, even more than twice that of conventional steel paper. The thickness of the steel paper of the present invention is not limited and can be any desired thickness. Exemplarily, the thickness of the environmentally friendly high-insulation steel paper of the present invention is 0.02-5 mm, such as 0.5 mm, 0.6 mm, 0.8 mm, 1 mm, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm, 2.0 mm, 2.5 mm, 3.0 mm, 3.5 mm, 4.0 mm, 4.5 mm, etc. It should be noted that the above thickness range is only an exemplary thickness, and those skilled in the art can produce steel paper beyond the above thickness range as needed.
[0057] In certain embodiments, the density of the steel paper of the present invention is not specific. Under the same conditions, the steel paper of the present invention has a higher density than the traditional steel paper. The exemplary density of the steel paper of the present invention is generally 1-2.5 kg / dm 3 , for example 1.2-2.4kg / dm 3 1.4-2.2kg / dm 3 1.5-2.0kg / dm 3 1.6-1.8kg / dm 3 wait.
[0058] Environmentally friendly fiber layer
[0059] In the present invention, the environmentally friendly fiber layer is not particularly limited as long as it includes jute fibers. Exemplarily, the environmentally friendly fiber layer of the present invention is a jute fiber net or a jute fiber cloth, wherein the jute fiber content is 70% by weight or more, preferably 80% or more, more preferably 90% or more, and most preferably 100%.
[0060] The jute fiber net of the present invention refers to a regular mesh structure or an irregular network structure formed by interweaving jute fibers. This structure not only ensures the strength of the material, but also allows the adhesive to penetrate into the gaps or interior of the mesh structure, making the bonding more sufficient, thereby improving the bonding. In certain embodiments, the adhesive layer of the present invention and the jute fiber net form a mixed layer.
[0061] Adhesive layer
[0062] The bonding layer of the present invention is formed by contacting and curing a bonding agent precursor with a steel paper layer or an environmentally friendly fiber layer.
[0063] The binder precursor of the present invention refers to a composition before forming a bonding layer, which comprises a phenolic resin and / or a latex emulsion, an organic solvent and a crosslinking agent, wherein the crosslinking agent is an optional component and is not a necessary component of the bonding layer precursor.
[0064] Among the present invention, the consumption of phenolic resin and / or latex emulsion is generally 70-85 weight parts, for example 75 weight parts, 80 weight parts, 85 weight parts etc. Then can be beneficial to form bonding layer in the above-mentioned scope.If the consumption is too low, then the removal cost of solvent increases after solidification.On the other hand, if the consumption is too high, then the viscosity is too high and the bonding property is affected.Phenolic resin and / or latex emulsion are preferably light-cured type.Phenolic resin of the present invention comprises resol phenolic resin and / or novolac resin.
[0065] In an exemplary embodiment, the resol resin of the present invention comprises an alkali catalyst, thereby accelerating the reaction and increasing the polymerization rate. Here, the alkali catalyst is any reagent known in the art, examples of which include but are not limited to sodium hydroxide, potassium hydroxide, calcium hydroxide, magnesium hydroxide and barium hydroxide. The present invention can use one of the above substances or use any combination of multiple. The amount of the alkali catalyst is generally 0-5% by weight.
[0066] In an exemplary embodiment, the latex emulsion of the present invention is a curable emulsion, such emulsions are known in the art, examples of which include curable latex emulsions derived from styrene, butadiene, acrylonitrile, chloroprene rubber, polyvinyl acetate, acrylate, acrylamide or copolymers thereof.
[0067] In the present invention, the amount of organic solvent is generally 25-30 parts by weight, for example, 26 parts by weight, 28 parts by weight, 29 parts by weight, etc. If the amount is too high, the cohesiveness tends to decrease. On the other hand, if the amount is too low, the curing property is affected, which is not conducive to the improvement of cohesiveness. Organic solvents suitable for the present invention include alcohols or ketones, such as methanol, ethanol, propanol, acetone, butanone, etc. The present invention can use one or more arbitrary combinations of the above-mentioned solvents. It should be noted that the organic solvent of the present invention does not include water or aqueous solvents.
[0068] In the present invention, the crosslinking agent is an optional component, and its usage is generally 0-5 parts by weight, for example, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, etc. The crosslinking agent can use any component known in the art, and its examples include but are not limited to melamine, polyepoxide, polyaziridine, urea formaldehyde resin, dicyandiamide, etc. The present invention can use a combination of one or more of the above substances.
[0069] It should be noted that the binder precursor in the present invention can penetrate or enter, for example, the interior or space of the environmentally friendly fiber web before curing, so that at least a portion of the binder of the present invention is mixed with the environmentally friendly fiber, and the wear resistance is greatly improved through the synergistic effect of the binder and the environmentally friendly fiber.
[0070] Fiberglass layer
[0071] The glass fiber layer of the present invention is an optional layer, which can be prepared using any known glass fiber. The glass fiber layer can be, for example, a glass fiber mesh or a glass fiber fabric. The glass fiber layer of the present invention can be arranged on the outer surface of the environmentally friendly fiber layer, or between the environmentally friendly steel paper layer and the environmentally friendly fiber layer.
[0072] The glass fiber layer of the present invention is combined with the environmentally friendly fiber layer and / or environmentally friendly steel paper layer through a binder precursor. The binder precursor can use the precursor described above, which will not be repeated here.
[0073] Treatment fluid
[0074] The treatment liquid of the present invention is used to treat the surface of the steel paper layer and / or the environmentally friendly fiber layer, so that the surface thereof has a hydrophobic structure. The treatment liquid of the present invention is an aqueous solution containing cerium salt and acrylamide.
[0075] In the present invention, the cerium salt is preferably a soluble salt, examples of which include but are not limited to cerium nitrate, cerium sulfate, cerium trichloride, cerium trichloride (III), cerium carbonate, cerium oxalate, cerium octoate, cerium cyclohexane acid, etc. The amount of the cerium salt is generally 0.1-2mM, preferably 0.2mM, 0.3mM, 0.4mM, 0.5mM, 0.6mM, 0.7mM, 0.8mM, 0.9mM, 1.0mM, 1.2mM, 1.4mM, 1.6mM, 1.8mM, etc. In the present invention, the amount of acrylamide is generally 20-50% based on the total weight of the aqueous solution, for example, 25%, 30%, 35%, 40%, 45%, etc.
[0076] In the present invention, the treatment step for the steel paper layer includes: applying the treatment liquid to one side of the steel paper, controlling the amount of the treatment liquid to be evenly maintained on the surface of the steel paper without overflowing, and controlling the temperature to be around 30°C for 1-4 hours, such as 1.5 hours, 2 hours, 3 hours, etc. Then, the steel paper is sequentially transferred to a solution containing diphenol for 1-5 minutes, neutralized with a 5% alkali solution for 1-2 minutes, washed with water and then dried.
[0077] In the present invention, the treatment step for the environmentally friendly fiber layer includes: treating the environmentally friendly fiber layer in different reaction tanks in turn, wherein the first reaction tank contains a treatment solution, and the treatment temperature is about 30°C for 1-4 hours, such as 1.5 hours, 2 hours, 3 hours, etc. The second reaction tank is a solution containing diphenol, and the treatment time is 1-5 minutes. The third reaction tank is a 5% alkali solution, and the treatment time is 1-2 minutes. The fourth reaction tank is pure water, and the treatment time is 10-60 minutes. After treatment, the environmentally friendly fiber layer is dried to control the water content to be less than 5%, preferably less than 3%, and more preferably less than 1%.
[0078] Granular layer
[0079] The particle layer of the present invention is an optional layer, which is arranged on the outer side of the environmentally friendly fiber layer, that is, on the side opposite to the bonding layer. After the particle layer is arranged, the laminated composite sheet can be used as an abrasive to make abrasive products.
[0080] In the present invention, the particle layer is formed by solidifying and pressing the particles containing the binder precursor and dispersed therein. The binder precursor here can be the same as the above-mentioned binder precursor, and will not be repeated here. The particles in the present invention can be selected from known products in the field of abrasives, and examples thereof include but are not limited to corundum, diamond, aluminum oxide, silicon carbide, zirconium oxide, cerium dioxide, titanium diboride, cubic boron nitride, boron carbide and flint. The present invention can use one or more combinations thereof.
[0081] In the present invention, the number of the particle layer is not limited, and it can be one layer or multiple layers, such as two layers. In the case of multiple layers, the composition of each layer can be the same or different, and there is no limitation on this. In the case of multiple layers, each layer is bonded and pressed together by an adhesive to form a firm bond.
[0082] Example 1
[0083] 1. Steel paper layer
[0084] 1. Raw material composition
[0085] Raw material composition:
[0086] Long fiber: absorbent cotton fiber, length 5-6mm, total fiber weight accounts for 95%;
[0087] Short fiber: wood pulp fiber, with a length of 1-2mm, a Kappa number of 8, and a total fiber weight of 5%.
[0088] 2. Preprocessing
[0089] After mixing in proportion, water is added and steamed for 1 hour to allow the fiber to fully absorb water and swell, while removing impurities. Next, the slurry enters the beater for beating treatment to further disperse and refine the fiber, with a beating degree of about 18°SR and a wet weight of about 10g.
[0090] 3. Paper
[0091] The pre-treated slurry then enters the slurry mixing box for mixing to ensure uniform slurry. It is further transported to the slurry mixing box for dilution to adjust the slurry concentration and purified to further remove impurities.
[0092] The diluted and purified pulp is dehydrated through the paper machine mesh, and then further dehydrated in the pressing section. It is then sent to the drying section for drying to control the water content in the range of 4-8% to obtain steel paper base paper.
[0093] The obtained multi-layer steel paper base paper is simultaneously conveyed by a conveying roller into a potion (68% zinc chloride) for immersion for 1.5 minutes to fully swell and gelatinize the fibers, promote the connection between the fibers, and thus improve the strength and stability of the steel paper. Next, the soaked multi-layer base paper is heated at 30-40°C for 20-30 minutes to further penetrate the zinc chloride and gelatinize the fibers. Then, the multi-layer base paper is subjected to hot pressing to tightly bond the multi-layer base paper to form a semi-finished product.
[0094] 4. Post-processing
[0095] The semi-finished product is sent to an aging furnace and aged at 20-40°C for about 50 minutes to improve the stability of the internal structure of the steel paper.
[0096] After aging, the steel paper is sequentially placed in multiple cleaning tanks with gradually decreasing concentrations and finally pure water for desalination treatment. The zinc chloride concentrations in the cleaning tanks are 60%, 30%, 15%, 8%, 4%, 2%, 1%, 0.5%, 0.05%, and 0. The desalination treatment time of each cleaning tank is controlled at 20-60 minutes, thereby making the surface of the steel paper smoother and more delicate. The steel paper is dried to obtain a thickness of about 3mm.
[0097] 2. Environmentally friendly fiber layer
[0098] The jute fiber net is conveyed into a treatment tank containing a treatment solution (containing 0.4mM cerium salt and 40% acrylamide aqueous solution) through a conveyor mechanism and treated at 30°C for about 2 hours. Next, it is conveyed into a solution containing 10% hydroquinone at room temperature for 1 minute. Then it is conveyed into a 5% sodium hydroxide solution for 1 minute. Subsequently, it is conveyed into a water tank for washing, stirring while washing, and the treatment time is 30 minutes. Finally, it is conveyed into the drying section for drying, and the water content is controlled to be about 3%.
[0099] 3. Laminated composite sheet
[0100] A proper amount of adhesive liquid is coated on the surface of the steel paper, and the jute fiber mesh is covered on the steel paper coated with the adhesive liquid, and a laminated composite sheet with a thickness of about 6 mm is obtained by pressing and curing. The adhesive liquid contains 75% phenolic resin and 25% ethanol.
[0101] Example 2
[0102] 1. Steel paper layer
[0103] 1. Raw material composition
[0104] Raw material composition:
[0105] Long fiber: absorbent cotton fiber, with a length of 5-6mm and a total fiber weight of 90%;
[0106] Short fiber: wood pulp fiber, with a length of 1-2mm, a Kappa number of 8, and a total fiber weight of 10%.
[0107] 2. Preprocessing
[0108] After mixing in proportion, water is added and steamed for 1 hour to allow the fiber to fully absorb water and swell, while removing impurities. Next, the slurry enters the beater for beating treatment to further disperse and refine the fiber, with a beating degree of about 15°SR and a wet weight of about 8g.
[0109] 3. Paper
[0110] The pre-treated slurry then enters the slurry mixing box for mixing to ensure uniform slurry. It is further transported to the slurry mixing box for dilution to adjust the slurry concentration and purified to further remove impurities.
[0111] The diluted and purified pulp is dehydrated through the paper machine mesh, and then further dehydrated in the pressing section. It is then sent to the drying section for drying to control the water content in the range of 4-8% to obtain steel paper base paper.
[0112] The obtained multi-layer steel paper base paper is simultaneously conveyed by a conveying roller into a potion (68% zinc chloride) for immersion for 1.5 minutes to fully swell and gelatinize the fibers, promote the connection between the fibers, and thus improve the strength and stability of the steel paper. Next, the soaked multi-layer base paper is heated at 30-40°C for 20-30 minutes to further penetrate the zinc chloride and gelatinize the fibers. Then, the multi-layer base paper is subjected to hot pressing to tightly bond the multi-layer base paper to form a semi-finished product.
[0113] 4. Post-processing
[0114] The semi-finished product is sent to an aging furnace and aged at 20-40°C for about 50 minutes to improve the stability of the internal structure of the steel paper.
[0115] After aging, the steel paper is sequentially placed in multiple cleaning tanks with gradually decreasing concentrations and finally pure water for desalination treatment. The zinc chloride concentrations in the cleaning tanks are 60%, 30%, 15%, 8%, 4%, 2%, 1%, 0.5%, 0.05%, and 0. The desalination treatment time of each cleaning tank is controlled at 20-60 minutes, thereby making the surface of the steel paper smoother and more delicate. The product is dried and has a thickness of 3mm.
[0116] 2. Environmentally friendly fiber layer
[0117] The jute fiber net is conveyed into a treatment tank containing a treatment solution (containing 0.5mM cerium salt and 45% acrylamide aqueous solution) through a conveying mechanism and treated at 30°C for about 2 hours. Next, it is conveyed into a solution containing 10% hydroquinone at room temperature for 1 minute. Then it is conveyed into a 5% sodium hydroxide solution for 1 minute. Subsequently, it is conveyed into a water tank for washing, stirring while washing, and the treatment time is 30 minutes. Finally, it is conveyed into the drying section for drying, and the water content is controlled to be about 3%.
[0118] 3. Laminated composite sheet
[0119] An appropriate amount of adhesive liquid is applied on the surface of the steel paper, and the jute fiber mesh is covered on the steel paper coated with the adhesive liquid, and a laminated composite sheet with a thickness of about 6 mm is obtained by pressing and curing. The adhesive liquid contains 75% phenolic resin, 24% ethanol and 1% melamine.
[0120] Example 3
[0121] 1. Steel paper layer
[0122] 1. Raw material composition
[0123] Raw material composition:
[0124] Long fiber: absorbent cotton fiber, length 5-6mm, total fiber weight accounts for 95%;
[0125] Short fiber: wood pulp fiber, with a length of 1-2mm, a Kappa number of 8, and a total fiber weight of 5%.
[0126] 2. Preprocessing
[0127] After mixing in proportion, water is added and steamed for 1 hour to allow the fiber to fully absorb water and swell, while removing impurities. Next, the slurry enters the beater for beating treatment to further disperse and refine the fiber, with a beating degree of about 18°SR and a wet weight of about 10g.
[0128] 3. Paper
[0129] The pre-treated slurry then enters the slurry mixing box for mixing to ensure uniform slurry. It is further transported to the slurry mixing box for dilution to adjust the slurry concentration and purified to further remove impurities.
[0130] The diluted and purified pulp is dehydrated through the paper machine mesh, and then further dehydrated in the pressing section. It is then sent to the drying section for drying to control the water content in the range of 4-8% to obtain steel paper base paper.
[0131] The obtained multi-layer steel paper base paper is simultaneously conveyed by a conveying roller into a potion (68% zinc chloride) for immersion for 1.5 minutes to fully swell and gelatinize the fibers, promote the connection between the fibers, and thus improve the strength and stability of the steel paper. Next, the soaked multi-layer base paper is heated at 30-40°C for 20-30 minutes to further penetrate the zinc chloride and gelatinize the fibers. Then, the multi-layer base paper is subjected to hot pressing to tightly bond the multi-layer base paper to form a semi-finished product.
[0132] 4. Post-processing
[0133] The semi-finished product is sent to an aging furnace and aged at 20-40°C for about 50 minutes to improve the stability of the internal structure of the steel paper.
[0134] After aging, the steel paper is sequentially placed in multiple cleaning tanks with gradually decreasing concentrations and finally pure water for desalination treatment. The zinc chloride concentrations in the cleaning tanks are 60%, 30%, 15%, 8%, 4%, 2%, 1%, 0.5%, 0.05%, and 0. The desalination treatment time of each cleaning tank is controlled at 20-60 minutes, thereby making the surface of the steel paper smoother and more delicate. The steel paper is dried to obtain a thickness of about 3mm.
[0135] 2. Treatment of treatment fluid
[0136] The jute fiber net is conveyed into a treatment tank containing a treatment solution (containing 0.4mM cerium salt and 40% acrylamide aqueous solution) through a conveyor mechanism and treated at 30°C for about 2 hours. Next, it is conveyed into a solution containing 10% hydroquinone at room temperature for 1 minute. Then it is conveyed into a 5% sodium hydroxide solution for 1 minute. Subsequently, it is conveyed into a water tank for washing, stirring while washing, and the treatment time is 30 minutes. Finally, it is conveyed into the drying section for drying, and the water content is controlled to be about 3%.
[0137] Spray the treatment liquid on one side of the steel paper, control the amount of addition so that it is always evenly maintained on the steel paper surface, and continue at a temperature of about 30°C for 1 hour. Next, transfer it into a solution containing 10% hydroquinone at room temperature for 30 seconds. Then continue to transfer it into a 5% sodium hydroxide solution for 30 seconds. Subsequently, transfer it into a water tank for washing for 1 minute. Finally, transfer it into the drying section for drying treatment, and control the water content to about 3%.
[0138] 3. Laminated composite sheet
[0139] A proper amount of adhesive liquid is coated on the surface of the steel paper, and the jute fiber mesh is covered on the steel paper coated with the adhesive liquid, and a laminated composite sheet with a thickness of about 6 mm is obtained by pressing and curing. The adhesive liquid contains 75% phenolic resin and 25% ethanol.
[0140] Example 4
[0141] 1. Steel paper layer
[0142] Same as Example 1.
[0143] 2. Environmentally friendly fiber layer
[0144] Same as Example 1.
[0145] 3. Laminated composite sheet
[0146] A proper amount of adhesive liquid is coated on the steel paper surface, the jute fiber mesh is covered on the steel paper coated with the adhesive liquid, and then a proper amount of adhesive liquid is further coated on the jute fiber mesh, and a laminated composite sheet with a thickness of about 9 mm is obtained by pressing and curing. The adhesive liquid contains 75% phenolic resin and 25% ethanol.
[0147] Comparative Example 1
[0148] The steel paper layer is the same as that in Example 1, and the jute fiber web is not treated with the treatment liquid. An appropriate amount of adhesive liquid is coated on the steel paper surface, and the jute fiber web is covered on the steel paper coated with the adhesive liquid, and a laminated composite sheet with a thickness of about 6 mm is obtained by pressing and curing. The adhesive liquid contains 75% phenolic resin and 25% ethanol.
[0149] Comparative Example 2
[0150] The same as Comparative Example 1 except for the following differences: a glass fiber mesh is used instead of a jute fiber mesh. An appropriate amount of adhesive liquid is coated on the surface of the steel paper, and the glass fiber mesh is covered on the steel paper coated with the adhesive liquid, and a laminated composite sheet with a thickness of about 6 mm is obtained by pressing and curing. The adhesive liquid contains 75% phenolic resin, 25% ethanol and 1% cross-linking agent.
[0151] Test Case
[0152] The wear resistance of the sheet was measured by the weight method. Specifically, the sheet was worn in a rotary manner using an ML-100 abrasive wear tester, starting from the jute layer side, and the weight change before and after wear was measured to calculate the wear resistance. The parameters are as follows:
[0153] Load: 5N;
[0154] Disc speed: 60 rpm;
[0155] Wear time: 5 minutes (wear until the steel paper is exposed);
[0156] Abrasive sandpaper: diameter 260mm;
[0157] Sample size: 2 cm radius disk.
[0158] The wear rate G (g / cm) was calculated according to the following formula 2 ):
[0159] G = (m1-m2) / A;
[0160] Wherein, m1 and m2 represent the weight of the sheet before and after wear, g;
[0161] A represents the friction area of the sample, cm 2 .
[0162] The test results are shown in Table 1 below.
[0163] Table 1
[0164]
[0165] Although the present invention has been described with reference to exemplary embodiments, it should be understood that the present invention is not limited to the disclosed exemplary embodiments. Various adjustments or changes may be made to the exemplary embodiments of the present specification without departing from the scope or spirit of the present invention. The scope of the claims should be based on the broadest interpretation to cover all modifications and equivalent structures and functions.
Claims
1. Wear-resistant and environmentally friendly laminated composite sheet, characterized in that: It is composed of an environmentally friendly steel paper layer, an environmentally friendly fiber layer and a bonding layer located between the environmentally friendly steel paper layer and the environmentally friendly fiber layer, wherein: the environmentally friendly steel paper layer and the environmentally friendly fiber layer have a hydrophobic structure on one side in contact with the bonding layer, and the bonding layer is formed by curing a bonding liquid including phenolic resin and ethanol; The hydrophobic structure of the environmentally friendly steel paper layer is obtained by a method comprising the following steps: Apply the treatment liquid to one side of the steel paper, control the amount of addition so that it is evenly maintained on the steel paper surface without overflowing, and control the temperature at 30°C for 1-4 hours. Next, transfer the steel paper to a solution containing diphenol for 1-5 minutes, neutralize it in 5% alkali solution for 1-2 minutes, wash it with water and then dry it; The hydrophobic structure of the environmentally friendly fiber layer is obtained by a method comprising the following steps: The environmentally friendly fiber layer is sequentially placed in different reaction tanks for treatment, wherein the first reaction tank contains a treatment solution, the treatment temperature is 30°C for 1-4 hours, the second reaction tank is a hydroquinone solution, the treatment time is 1-5 minutes, the third reaction tank is a 5% alkali solution, the treatment time is 1-2 minutes, the fourth reaction tank is pure water, the treatment time is 10-60 minutes, and the environmentally friendly fiber layer is dried after treatment to control the water content to be less than 5%; Wherein, the treatment solution is an aqueous solution containing 0.1-2 mM cerium salt and 20-50% acrylamide; The environmentally friendly fiber layer is a jute fiber net made of 100% jute fiber; The raw materials of the environmentally friendly steel paper layer include 90-95 parts by weight of long fibers and 5-10 parts by weight of short fibers, wherein the long fibers are absorbent cotton fibers with a length of 5-6 mm, and the short fibers are wood pulp fibers with a length of 1-2 mm.
2. The wear-resistant and environment-friendly laminated composite sheet according to claim 1, characterized in that: The kappa number of the wood pulp fiber is 10-20.
3. The wear-resistant and environment-friendly laminated composite sheet according to claim 1, characterized in that: The bonding liquid comprises 70-85 parts by weight of phenolic resin, 25-30 parts by weight of ethanol and 0-5 parts by weight of a cross-linking agent.
4. The wear-resistant and environment-friendly laminated composite sheet according to claim 1, characterized in that: The phenolic resin includes a resol resin and / or a novolac resin.
5. A method for preparing a wear-resistant and environment-friendly laminated composite sheet, characterized in that: The composite sheet is composed of an environmentally friendly steel paper layer, a 100% jute fiber mesh as an environmentally friendly fiber layer, and a bonding layer located between the environmentally friendly steel paper layer and the environmentally friendly fiber layer, and the method comprises the following steps: (1) treating the environmentally friendly steel paper layer and the environmentally friendly fiber layer with a treatment solution, wherein the treatment solution contains 0.1-2 mM cerium salt and 20-50% acrylamide, and comprises: Apply the treatment liquid to one side of the steel paper, control the amount of addition so that it is evenly maintained on the steel paper surface without overflowing, and control the temperature at 30°C for 1-4 hours. Next, transfer the steel paper to a solution containing diphenol for 1-5 minutes, neutralize it in 5% alkali solution for 1-2 minutes, wash it with water and then dry it; The environmentally friendly fiber layer is sequentially placed in different reaction tanks for treatment, wherein the first reaction tank contains a treatment solution, the treatment temperature is 30° C. and lasts for 1-4 hours, the second reaction tank is a solution containing diphenol, the treatment time is 1-5 minutes, the third reaction tank is a 5% alkali solution, the treatment time is 1-2 minutes, and the fourth reaction tank is pure water, the treatment time is 10-60 minutes, and after the treatment, the environmentally friendly fiber layer is dried to control the water content to be less than 5%; and (2) Next, a bonding liquid is coated on the surface of the steel paper, and the environmentally friendly fiber layer is covered on the steel paper coated with the bonding liquid, and a laminated composite sheet is obtained by pressing and curing, wherein the bonding liquid comprises 70-85 parts by weight of a phenolic resin, 25-30 parts by weight of ethanol, and 0-5 parts by weight of a cross-linking agent; The raw materials of the environmentally friendly steel paper layer include 90-95 parts by weight of long fibers and 5-10 parts by weight of short fibers, wherein the long fibers are absorbent cotton fibers with a length of 5-6 mm, and the short fibers are wood pulp fibers with a length of 1-2 mm.
Citation Information
Patent Citations
Abrasive steel paperboard and manufacturing process thereof
CN103147356A
Elastic flap wheel
CN221792348U